If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 3 = 24 Reorder the terms: 3 + 6m = 24 Solving 3 + 6m = 24 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6m = 24 + -3 Combine like terms: 3 + -3 = 0 0 + 6m = 24 + -3 6m = 24 + -3 Combine like terms: 24 + -3 = 21 6m = 21 Divide each side by '6'. m = 3.5 Simplifying m = 3.5
| 209=m-354 | | 2(2X+10)=80 | | 3g=237 | | -2.4-4x-8.6-2x=-5x-7.3 | | 6p+3p-p= | | 9-5z=4 | | 2m^2-11m-115=6 | | -1.2x+0.4+6.4x-2.4=5-3.8x+4 | | 5z(-9)=4 | | 9h+h+2h= | | y^3-5y+5=0 | | 2x+3=-12x+1 | | (5x+4)=56 | | X=150-.2x | | -2-3+4=5-6x | | 10x-5-3(2x+5)=-20 | | 2(2x-5)+6(2x+6)=0 | | 9m-26=36 | | 25x^2+4y^2-6=0 | | f(0)=2(2x-5)+6(2x+6) | | 1/3*6= | | z+-40=36 | | 23-2(3+4)= | | 2(3x-1)-2x=7x+3 | | 3x+3=3x+15-5 | | 4+2X=10-4X | | 37x*0.6=77.7 | | Xy-3y-y=0 | | 2(5-8x)-5=5(2x+1) | | x^3+0x^2-3x+2=0 | | 14n=13a-11 | | w+-48=-23 |